DEVELOPMENT OF AN IMPROVED PRESSURE VARYING HYDRAULICALLY OPERATED AGRICULTURAL WASTE BRIQUETTING MACHINE - Kayode, Oke Peter; Gideon, Olaiya Niyi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2019)
In several developing countries, briquettes from agricultural residues contribute significantly to the energy mix especially for small scale and household requirements. Most times, these briquettes are produced from a manually operated briquetting machine where the pressure at which the agricultural waste is compressed cannot be ascertained. Therefore, this work deals with the design and fabrication of pressure varying hydraulically operated briquetting machine. This machine can produce sixteen (16) briquettes at a time. The machine was developed in other to reduce the stress of producing the briquette and to establish the optimum pressure at which the agricultural waste is compressed. The varying pressure at which the briquette is compressed was used to establish the effect of pressure on the calorific value of the briquette. The agricultural waste that was used for the briquette includes palm kernel shell, rice bran, and sawdust with cassava starch as the binder. Each agricultural waste particle was load in the machine mold at different times at varying pressure of 30, 70, and 100kg/cm2. The result shows that the briquette of sawdust has the highest heating value of 17.585 at 70kg/cm2 pressure while the highest value was recorded for rice bran as 13.722 at 100kg/cm2 and 18.342 MJ/kg at 100kg/cm2 pressure for palm kernel shell.